Public and private values - Dan Ariely; Anat Bracha; Jean-Paul L'Huillier (Federal Reserve Bank of Boston, 2010)
This paper experimentally examines whether looking at other peoples pricing decisions is a type of heuristic - a decisionmaking rule - that people use even when it is not applicable, as in the case of clearly private value goods. We find evidence that this indeed is the case - an individuals valuation of a purely subjective experience under full information, elicited using an incentive compatible mechanism, is highly influence by valuations made by others. This result can shed light on price behavior, price rigidities, and rents.
Keywords: J64; E24; J11; 330